Adaptive harmonic-based protection coordination for inverter-dominated isolated microgrids considering N-1 contingency - Talal Elemamali Sati; Maher A. Azzouz; Mostafa F. Shaaban (International Journal of Electrical Power & Energy Systems)
Protection coordination is typically approached considering the main network configuration. Nevertheless, contingencies such as generator or line failures may disrupt power grids. Low fault currents in inverter-based isolated microgrids adversely impact the conventional overcurrent protection schemes. This paper proposes a sensitive and selective protection scheme for isolated microgrids using an adaptive third harmonic voltage generated by inverter-based distributed generators (IBDGs) and adapted to fault severity. The generated harmonic voltage results in a harmonic layer established during faults and is decoupled from the fundamental fault current, which is limited by IBDGs. Harmonic directional overcurrent relays sense the generated harmonic currents and voltages at the relay location to ensure optimal protection coordination (OPC). The OPC problem is formulated as a constrained nonlinear program to determine the optimal relays’ settings. The constraints are defined for the isolated configuration and each potential configuration resulting from an N-1 contingency. A radial microgrid that is part of a Canadian urban distribution network is used to ensure the successful operation of the proposed protection scheme. The results demonstrate the ability of the proposed scheme to protect isolated microgrids and preserve protection coordination without communication.